UM CORPO, DO MAR ÀS MONTANHAS: QUESTÕES DE GÊNERO EM A AUTOBIOGRAFIA DA MINHA MÃE, DE JAMAICA KINCAID - Souza, Rafael Francisco Neves de (2024)
Understanding the significance of contemporary literary studies and their ethical and aesthetic dimensions, this research first highlights the path traced by decolonial feminism in the literary context, shedding light on how the role of women has been shaped under the shadow of oppressions stemming from colonization in Caribbean lands. In a second moment, as the main corpus for discussion, it examines the findings in The autobiography of my mother by Caribbean author Jamaica Kincaid (2020), and reflects on the portrayal of the main character, Xuela Claudette Richardson. This process occurs in the context of European colonial oppression, serving as a social and political critique of the historical silencing of colonial power present in the work. In this regard, we are interested in studies on feminist discussions, based on decolonial feminism and post colonialism, such as those by Françoise Vergès (2021), Djamila Ribeiro (2018), Lélia Gonzalez (2020), Heloisa Buarque de Hollanda (2021), Zilá Bernd (2018), Frantz Fanon (2008), Aimé Césaire (2020), among others, which shed light on the literary analysis of Jamaica Kincaid's work, allowing us to explore beyond Caribbean boundaries. Elements of transculturality, hybridization, alterity, and reactive othering constitute the literary texture of The autobiography of my mother (2020). These elements perform the ethical and poetic literature of the author. They are features found in a significant part of contemporary literature authored by women in the Americas and the Caribbean, as exemplified by Conceição Evaristo, Ana Maria Gonçalves, Djamila Ribeiro, Jarid Arraes, Glória Anzaldua, Maryse Condé, among many others. This research focuses on the process of retaliation narrated in the diegesis and reflects on how the female character is represented, highlighting alternative ways of survival for the Black feminine within the patriarchal system. Contemporary literature and essay production authored by Black women engage in dialogue with the struggles of these women, who face subjugation, particularly due to gender, race, and sexuality issues. In this sense, they represent women as agents of their own history, as they write literature and postcolonial theory. In the reflections and analyses of The autobiography of my mother, we emphasize the aesthetic resources employed by Jamaica Kincaid in the language of the text, which reveal the character Xuela Claudette Richardson, breaking away from a predetermined narrative that portrays her as a passive, submissive, and objectified woman, and showcasing the ethical and aesthetic project of the writer. Finally, this thesis is justified as a study that seeks to understand, analyze, and corroborate with the poetic writing of Jamaica Kincaid within the realm of Caribbean authors who produce their literary narratives in light of the stories of their ancestors and peoples during the period of Caribbean colonization, as exemplified by Dominica, where the studied diegesis unfolds.